Correction of prasugrel‐related bleeding by prophylactic transfusion of human platelets in a rabbit model. Issue 10 (21st August 2016) - Bonhomme, Fanny; Godier, Anne; Samama, Charles Marc; Lecompte, Thomas; Fontana, Pierre
Abstract : BACKGROUND: Prasugrel provides rapid and intense inhibition of platelet aggregation combined with an increased risk of bleeding. We evaluated the efficacy and safety of platelet transfusion to reduce blood loss after a prasugrel loading dose in a rabbit model. STUDY DESIGN AND METHODS: Thirty‐five rabbits were randomized into five groups: "control" (saline plus physiological buffer), "no‐transfusion" (prasugrel plus physiological buffer), "platelet low dose" (prasugrel loading dose plus transfusion with a platelet count increase <80 × 10 9 /L), "platelet intermediate dose" (prasugrel loading dose plus transfusion with a platelet count increase 80‐120 × 10 9 /L), and "platelet high dose" (prasugrel loading dose plus transfusion with a platelet count increase ≥120 × 10 9 /L). Naïve, washed human platelets in physiological buffer were transfused before bleeding was induced. Sequentially, a stenosis and an injury were carried out on the carotid artery to induce cyclic thrombotic occlusions. Ultimately, liver sections were performed to evaluate the primary endpoint of blood loss monitored for 15 minutes. RESULTS: Blood loss in the "control" group was 3.16 g/kg (inerquartile range [IQR] [4.79‐9.15]) and was increased in the "no‐transfusion" group to 6.15 g/kg (IQR [4.79‐9.15]; p < 0.02). There was a gradual trend across the three transfusion groups toward less bleeding, and the highest dose of platelet transfusion significantly decreased prasugrel‐induced blood loss (3.05 g/kg; IQR [2.55‐3.56]; p = 0.006). Platelet aggregation was significantly but only partially restored in the latter group. Regarding safety, platelet transfusion was not associated with an increase in thrombotic events regardless of the dose. CONCLUSIONS: In this animal model, platelet transfusion aiming for a platelet count increase of at least 120 × 10 9 /L was necessary to correct prasugrel‐related bleeding.